Linking Islamic Financial Literacy and MSMEs Performance: A Comprehensive Review - Fitriyah, Fitriyah; Winarno, Agung; Pratikto, Heri (Cita konsultindo, 2024)
This study aims to explore the role of Islamic financial literacy in improving MSME business performance through a systematic literature review approach. Islamic financial literacy is considered increasingly relevant in the context of Muslim-majority countries, especially in supporting sharia-compliant financial decision-making, such as avoiding usury and using profit-sharing-based financing. Based on a literature analysis of various scientific articles, this study found that Islamic financial literacy can have a positive impact on MSMEs' business performance, profitability and innovation. In addition, this study also identifies research gaps related to moderating factors, such as religiosity, financial inclusion and business scale that affect the effectiveness of Islamic financial literacy. The results of this study are expected to contribute to academics, practitioners and policy makers in designing strategies to improve Islamic financial literacy more effectively to support MSME business performance